FIGURES IN THE MIRE: TOWARDS TRANSFORMATIVE ART AND A RESPECTFUL MIRE RELATIONSHIP - Latvala-Harvilahti Pauliina (Folk Belief and Media Group of Estonian Literary Museum, 2025)
Mire art is a versatile form of ecologically engaged art that reflects images of the relationship with nature in its time. This article regards mire art as transformative art that links both to climate change and new ways of experiencing the mire. Mire art no longer reflects so much the aesthetics of the mire enjoyed by humans, but rather the mire aside from human activity and the importance of protecting mire nature in the climate crisis. My perspective on the transformative aspects of mire art stems from the artist’s choices, values and aims, which I explore by reflecting on both artist interview and my own ex- perience of the artwork on site. The theoretical approach combines the study of cultural meanings and knowledge inherent in ethnological case studies with the concepts of art research. Art interventions can play a transformative role which increases knowledge, trust, and social capital. The Invited Guests series (Fin. Kutsuvieraat, 2020) by visual artist Reetta Partanen in the city of Seinäjoki, Finland, is a sculptural series made of organic material. The artwork is situated in the pristine mire in South Ostrobothnia, where peatlands are still used for energy. The article asks how the artist and her artwork emphasize the value of the mire as a natural place and softly question the dominant place of humans in the world. Importantly, the materials in the work have been chosen not to be a burden on the environment, but rather to benefit nature. The research shows that transformative art highlights the agency of nature, and in this study, the artwork gives mire a level of attention that differs from that centered on com- mercial use.